Impact of postoperative morbidity on long‐term survival after oesophagectomy1. Issue 1 (12th November 2012) - Hii, M. W.; Smithers, B. M.; Gotley, D. C.; Thomas, J. M.; Thomson, I.; Martin, I.; Barbour, A. P.
Abstract Background: Oesophageal malignancy is a disease with a poor prognosis. Oesophagectomy is the mainstay of curative treatment but associated with substantial morbidity and mortality. Although mortality rates have improved, the incidence of perioperative morbidity remains high. This study assessed the impact of postoperative morbidity on long‐term outcomes. Methods: A prospective database was designed for patients undergoing oesophagectomy for malignancy from 1998 to 2011. An observational cohort study was performed with these data, assessing intraoperative technical complications, postoperative morbidity and effects on overall survival. Results: Some 618 patients were included, with a median follow‐up of 51 months for survivors. The overall complication rate was 64·6 per cent (399 of 618), with technical complications in 124 patients (20·1 per cent) and medical complications in 339 (54·9 per cent). Technical complications were associated with longer duration of surgery (308 min versus 293 min in those with no technical complications; P = 0·017), greater operative blood loss (448 versus 389 ml respectively; P = 0·035) and longer length of stay (22 versus 13 days; P < 0·001). Medical complications were associated with greater intraoperative blood loss (418 ml versus 380 ml in those with no medical complications; P = 0·013) and greater length of stay (16 versus 12 days respectively; P < 0·001). Median overall and disease‐free survival were 41 and 43 months. After controlling for age, tumour stage, resection margin, length of tumour, adjuvant therapy, procedure type and co‐morbidities, there was no effect of postoperative complications on disease‐specific survival. Conclusion: Technical and medical complications following oesophagectomy were associated with greater intraoperative blood loss and a longer duration of inpatient stay, but did not predict disease‐specific survival. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.